Synthesis and investigation on microstructural, mechanical features of mesoporous hardystonite/reduced graphene oxide nanocomposite for medical applications - Bagherpour, Iman; Yaghtin, Amirhossein; Naghib, Seyed Morteza; Molaabasi, Fatemeh (Frontiers in Bioengineering and Biotechnology, 2023)
The use of hardystonite (Ca2ZnSi2O7, HT)-based composites could be one the main strategies to improve mechanical properties closing to natural bone. However, there are a few reports in this regard. Recent findings indicate that graphene is a promising biocompatible additive in ceramic-based composite. Here, we propose a simple approach for the synthesis of porous nano- and microstructured hardystonite/reduced graphene oxide (HT/RGO) composite using a sol-gel method followed by ultrasonic and hydrothermal processes. Integrating GO to the pure HT increased the bending strength and toughness values about 27.59% and 34.33%, respectively. It also allowed the increment of compressive strength and compressive modulus by about 8.18% and 86%, respectively and improvement in the fracture toughness about 11.8 times compared to pure HT. The formation of HT/RGO nanocomposites with different RGO weight percentages ranging from 0 to 5.0 has been investigated by scanning electron microscopy (SEM) and X-ray diffraction. The cell viability of HT/RGO composites was assayed by methyl thiazole tetrazolium (MTT) test in vitro. In this regard, the adhesion of human osteoblast cells (hFOB) on the 1% wt. HT/RGO composites was showed the best results. In addition, the alkaline phosphatase (ALP) activity and the proliferation rate of cells on the HT/1 wt. % RGO composites enhanced in comparison with the pure HT ceramic. These results suggest that bioceramic hardystonite/reduced graphene oxide composites can be a promising candidate for designing hard tissue implants.